Money illusion in the stock market the Modigliani-Cohn hypothesis - Cohen, Randolph B.; Polk, Christopher; Vuolteenaho, Tuomo (National Bureau of Economic Research, 2005)
"Modigliani and Cohn [1979] hypothesize that the stock market suffers from money illusion, discounting real cash flows at nominal discount rates. While previous research has focused on the pricing of the aggregate stock market relative to Treasury bills, the money-illusion hypothesis also has implications for the pricing of risky stocks relative to safe stocks. Simultaneously examining the pricing of Treasury bills, safe stocks, and risky stocks allows us to distinguish money illusion from any change in the attitudes of investors towards risk. Our empirical resuts support the hypothesis that the stock market suffers from money illusion"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Stocks -- Econometric models